Current state and trends in tramp ship routing and scheduling - Hannah Pache; Marvin Kastner; Carlos Jahn (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: This paper discusses the current state of routing and scheduling in tramp shipping, an important planning problem on the operational level in maritime logistics. The purpose is to report and compare the existing methods and to investigate possible future additions and improvements. Furthermore, an outlook on potential applications of machine learning for this optimization problem is given. Methodology: In this paper an extensive literature review of reports and journal papers on cargo routing in tramp shipping of the last seven years is conducted. The wide range of findings are categorized by the different considered characteristics. The results are analyzed and trends are pointed out. Findings: Optimization problems in tramp shipping differ in their main properties from liner shipping or classical vehicle routing problems. Thus, different approaches and implementations are required when developing or adapting existing optimization algorithms. The real-world problem is often limited in the optimization, so found solutions are improvements, but cannot fully reflect reality yet. Originality: This paper provides a comprehensive overview of tramp ship routing and scheduling. Although optimization of routing and scheduling in liner shipping is fairly well researched, the publications on tramp shipping are sparse in comparison. This leaves room for future research, as the findings for liner shipping and vehicle routing are not directly applicable to tramp shipping.
urn:nbn:de:gbv:830-882.054938; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Tramp shipping; Routing and scheduling; Maritime transportation; Cargo routing